Social realism and commitment in husah al-tuwayjir’ wa tula sh‘an min jadidin (2014)
This paper examines the short story written by Husah al-Tuwayjir entitled " Wa (ala Sh ‘an niin jadidin (And My Hair Grew Long Again). The work belongs to that rare category of Saudi Arabian female fiction writers which offers female perspectives to the general corpus of modern Arabic literary repertoire. The paper explores the expansive articulation of female identity that is contested as a negative model in the story and also points to the social and feminist commitment in Arab-Muslim societies, especially in Saudi Arabia. The short fiction written by alTuwayjir, the paper argues, accounts for female experiences that reduce male-female relationships in the given social context to a fundamentally antagonistic one. Al-Tuwayjir’s story is unabashedly a case study of a more convinced but also matter of fact and multifaceted perspective on female experience in the Arabian Peninsula.